Dance flashmob as sociocultural phenomenon: screen image and reality behind the screen / ТАНЦЕВАЛЬНЫЙ ФЛЕШМОБ КАК СОЦИОКУЛЬТУРНОЕ ЯВЛЕНИЕ: ЭКРАННЫЙ ОБРАЗ И ВНЕЭКРАННАЯ РЕАЛЬНОСТЬ - PLATONOVA O.A. / ПЛАТОНОВА О.А. (Наука телевидения, 2017)
The article is devoted to such modern youth phenomenon as a flashmob, i.e. in advance planned mass action organized with the definite purpose known only to organizers and participants, but which seems unusual, spontaneously arisen, short-term action. Besides the classical flashmob breaking the daily routine, the author allocates some other “variations”. X-mob, not scripted, or real, a flashmob where, apparently, usual actions of participants (they stumble, read, glue announcements), their anonymity cause feeling of a certain psychological game. L-mob (Long-mob) where each mobber can make in advance planned actions almost at any convenient time, and in any convenient place. I-mob—flashmobs held on the Internet. Political-mob and socio-mob—a way of expression of own political and social position, modern alternative to meetings and demonstrations. Advertising-mob where the style of a flashmob is used to draw attention to any brand or to a company. Art-mob—a flashmob with some certain art properties attracting the viewer. A special case of an art-mob is a dancing flashmob. This spectacular dancing mass action existing on a joint of art, entertainment and social event, is usually held in crowded places. Participants of a dancing flashmob are mainly active part of the population (students of high schools and the working youth, representatives of creative organizations, dance schools, etc.). The author analyzes the structure of a flashmob, emphasizing the general and individual similarities and distinctions between a dancing flashmob and a classical flashmob. The analysis mentions a screen image, organizational structure, participants, means of distribution of information, aims, tasks, stages of organization and implementation of an idea. As a result, the author comes to the conclusion that some “aberrations”, which can be found during flashmobs, in most cases don’t affect deep bases of the sociocultural phenomenon itself. The principles of spontaneity and surprise, lack of communication between mobbers during an action are firm. Motives and purposes of participants are still sincere, for them a flashmob is a symbol of creativity, enthusiasm, communication and self-affirmation. Only time will show, whether the flashmob is on the way to approach socio- and even political-mob, whether it will choose an art form, having approached performance, or it will become a part of profitable business?